2022
DOI: 10.1002/hbm.26182
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sex, age, general cognition and mental health with machine learning on brain structural connectomes

Abstract: There is an increasing expectation that advanced, computationally expensive machine learning (ML) techniques, when applied to large population‐wide neuroimaging datasets, will help to uncover key differences in the human brain in health and disease. We take a comprehensive approach to explore how multiple aspects of brain structural connectivity can predict sex, age, general cognitive function and general psychopathology, testing different ML algorithms from deep learning (DL) model (BrainNetCNN) to classical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 112 publications
1
3
0
Order By: Relevance
“…Therefore, to further evaluate the relevance of demographic variables in the prediction setting we investigated the individual contributions of age, sex, and education to the prediction by including these as extra features to the ML model. We found that the addition of age, sex, and education to our brain models drastically increased predictability of cognitive targets, in line with prior studies [31,32,55,106,107]. For example, Dadi et al showed that fluid intelligence and neuroticism were more successfully predicted when sociodemographic information was included into the model in a large sample from the UK Biobank (N = 11,175) [31].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, to further evaluate the relevance of demographic variables in the prediction setting we investigated the individual contributions of age, sex, and education to the prediction by including these as extra features to the ML model. We found that the addition of age, sex, and education to our brain models drastically increased predictability of cognitive targets, in line with prior studies [31,32,55,106,107]. For example, Dadi et al showed that fluid intelligence and neuroticism were more successfully predicted when sociodemographic information was included into the model in a large sample from the UK Biobank (N = 11,175) [31].…”
Section: Discussionsupporting
confidence: 88%
“…We also found septum and fimbria among relevant nodes. Differences in these structures (Yeung, Stolicyn et al 2023) have been reported (Xin, Zhang et al 2019). We also found differences in hypothalamus, a well-known sexually dimorphic region (Scott, Prigge et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…the basal ganglia, hypothalamus (48[45], hippocampus, and amygdala [46]. Memory related circuits (including the entorhinal cortex, hippocampus, septum and fimbria [47] [48], were supplemented with cerebellum and gigantocellular nuclei circuits, suggesting differences in locomotor recovery after injury[39] [49].…”
Section: Discussionmentioning
confidence: 99%
“…They attributed this improvement to the ability of BrainNetCNN to extract hierarchical features from the functional connectome, including both global and local network properties. Another study also used BrainNetCNN for brain age prediction and found that it was able to capture nonlinear relationships between the functional connectivity patterns and brain age [27]. They suggested that this was due to the ability of BrainNetCNN to learn more complex and diverse features from the functional connectome.…”
Section: Discussionmentioning
confidence: 99%